INACCURATE USE OF PUNCTUATION IN WRITING ACADEMIC DEGREES ON POSTERS AND BANNERS - Ertinawati, Yuni; Auzia, Asti Gea; Rahmaniar, Nabila; Pramesti , Tiara Rosanda (Media Inovasi Pendidikan dan Publikasi, 2024)
This research begins with the discovery that there are punctuation errors in academic degrees that make the meaning of the degree wrong. Academic degree writing is often neglected in terms of punctuation accuracy, causing confusion and obscurity in understanding one's degree. The purpose of this research is to identify punctuation errors in the writing of academic degrees as well as to conduct a correction process on the form of degree writing errors following the rules for writing academic degrees in Indonesia stipulated in the General Guidelines for Indonesian Spelling (PUEBI). The results of our research show that academic degrees are not written with a full stop between abbreviated letters and do not end with a full stop. This research is useful to be able to educate readers about the correct procedure for writing punctuation marks on academic degrees according to applicable rules.The data collection technique is carried out by searching for information on the internet which is used as the object of this research. The conclusion of this research is the wrong use of punctuation marks such as full stops and commas that do not pay attention to any errors in writing academic degrees